KELAYAKAN USAHA DAN EFISIENSI PEMASARAN AYAM BURAS DI KECAMATAN DUSUN TENGAH KABUPATEN BARITO TIMUR - Gajiansyah Gajiansyah; Asnah Asnah (BUANA SAINS, 2006)
A study that as aimed to elucidate farming and marketing efficiencies of indigenous and intensive poultry farming was carried out at Dusun Tengah District of Barito Timur Regency. One hundred fifty four farmers was grouped into two groups, i.e. ordinary farmers having traditional poultry farming and leading farmers having intensive farming. Fifteen samples were then randomly selected from each group summing 30 samples. Trader samples were determined using a non probability sampling method. Primary data was directly collected from farmer samples through interview. Data analyses covered farming feasibility that was measured using RCR (revenue cost ratio), effect of marketing cost that included costs of transportation, labour, retribution, risk and capital interest on profit of traders, marketing margin, vertical market integration and price transmission elasticity. Results of this study showed that intensive farming of indigenous poultry gave profit twice higher than that of traditional farming. However, intensive farming was more profitable than traditional farming. There were five marketing channels of indigenous poultry involving farmers and traders. The greatest margin distribution at most marketing channels was recieved by traders. Marketing costs simultaneously gave signicifant affect to profit made by traders. Price at farmer level with that of consumer level was not yet vertically integrated so that full competition of market structure has not developed